Rae-Ann M.K. Santos Family Photograph During COVID-19 - Santos, Rae-Ann M. K.::::::::: (2021)
Photograph of Rae-Ann Santos and father, Erick Santos, taken at Costco in Hayward, California on May 7, 2020.